Evaluating the inclusion level of medium chain fatty acids to reduce the risk of PEDV in feed and spray-dried animal plasma - Cochrane, R. A.; Saensukjaroenphon, M.; Dritz, Steven S.; Woodworth, Jason C.; Huss, A. R.; Stark, Charles R.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Bai, Jianfa; Chen, Q.; Zhang, J.; et al. (My University, 2016)
Research has confirmed that chemical treatments, such as medium chain fatty acids (MCFA) and commercial formaldehyde, can be effective to reduce the risk of porcine epidemic diarrhea virus (PEDV) cross-contamination in feed. However, the efficacy of MCFA levels below 2% inclusion is unknown. The objective of this experiment was to evaluate if a 1% inclusion of MCFA is as effective at PEDV mitigation as a 2% inclusion or formaldehyde in swine feed and spray-dried animal plasma (SDAP). Treatments were arranged in a 4 × 2 × 6 plus 2 factorial with 5 chemical treatments: 1) PEDV positive with no chemical treatment, 2) 0.325% commercial formaldehyde, 3) 1% MCFA, and 4) 2% MCFA; 2 matrices: 1) complete swine diet and 2) SDAP; 6 analysis days: 0, 1, 3, 7, 14, and 21 post inoculation; and 1treatment each of PEDV negative untreated feed and plasma. Matrices were first chemically treated, then inoculated with PEDV, and stored at room temperature until being analyzed by RT-qPCR. Data were analyzed by the GLIMMIX procedure of SAS. The analyzed values represent threshold cycle (CT), at which a higher CT value represents less detectable RNA. All main effects and interactions except for day × form were significant (P < 0.02). Feed treated with MCFA, regardless of inclusion level, had fewer (P < 0.05) viral particles than feed treated with formaldehyde. However, the SDAP-treated with either 1% or 2% MCFA had similar (P > 0.05) concentrations of detectable PEDV RNA as the untreated SDAP, while the SDAP treated with formaldehyde had fewer viral particles (P < 0.05). The complete feed had a lower (P < 0.05) quantity of PEDV RNA than SDAP (34.2 vs. 32.2 for feed vs. SDAP, respectively) (P < 0.05). Analysis day also decreased (P < 0.05) the quantity of detectable viral particles from d 0 to d 21, (33.2 vs. 39.0, respectively). In summary, time, formaldehyde, and MCFA all appear to enhance RNA degradation of PEDV in swine feed and ingredients, but their effectiveness varies within matrix. The 1% inclusion level of MCFA was as effective as 2% in complete feed, but neither was effective at reducing the magnitude of PEDV RNA in SDAP.
Citation: Cochrane, R. A., Saensukjaroenphon, M., Dritz, S. S., Woodworth, J. C., Huss, A. R., Stark, C. R., . . . Jones, C. K. (2016). Evaluating the inclusion level of medium chain fatty acids to reduce the risk of PEDV in feed and spray-dried animal plasma. Journal of Animal Science, 94, 50-50. doi:10.2527/msasas2016-107
Additional Authors: Main, R.
Keywords: Feed Matrix; Medium Chain Fatty Acids; Ped; Agriculture